2007
DOI: 10.1590/s1516-14392007000100015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of asphalt-rubber rotational viscosity by statistical analysis and neural networks

Abstract: It is of a great importance to know binders' viscosity in order to perform handling, mixing, application processes and asphalt mixes compaction in highway surfacing. This paper presents the results of viscosity measurement in asphalt-rubber binders prepared in laboratory. The binders were prepared varying the rubber content, rubber particle size, duration and temperature of mixture, all following a statistical design plan. The statistical analysis and artificial neural networks were used to create mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Overall, there were significant differences in viscosity between modified binder containing additive and one without additive. Rheology performance is very important in order to study the influence of mixing process and condition to the non solid material characteristic [11]. The effect of warm mix additive on Natural Rubber Modified Bitumen on the complex modulus (G*) which is related to the viscoelasticity property is illustrated in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there were significant differences in viscosity between modified binder containing additive and one without additive. Rheology performance is very important in order to study the influence of mixing process and condition to the non solid material characteristic [11]. The effect of warm mix additive on Natural Rubber Modified Bitumen on the complex modulus (G*) which is related to the viscoelasticity property is illustrated in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the temperature susceptibility of the bitumen samples has been calculated in terms of penetration index (PI) using the results obtained from penetration and softening point tests [35] The viscosity is defined as resistance of a fluid to flow and it affects the workability of the bitumen [36]. Brookfield viscometer was employed to inspect the mixing and compaction temperatures of the mixtures in according to ASTM D4402-06 [37].…”
Section: Test Methods 221 Conventional Bitumen Testsmentioning
confidence: 99%
“…The statistical analysis and artificial neural networks were used to create mathematical models for the prediction of the bitumen viscosity. The comparison between experimental data and simulated results with the generated models exhibited best performance of the neural networks analysis in contrast to the statistic models [15]. It was reported that the ANN model gives satisfactory results for estimating the deflection of pavement according to layer thickness [16].…”
Section: Introductionmentioning
confidence: 90%